Protocolo multiciclos para automação hospitalar sobre Multicast com IEEE 802.3 utilizando - Valentim, Ricardo Alesxandro de Medeiros (2008)
The concepts of the industrial automation are being incorporated in the medical area, in other words, they also pass to be applied in the hospital automation. In this sense, researches have been developed and have usually been approached several of the problems that are pertinent to the processes that can be automated in the hospital environment. Considering that in the automation processes, an imperative factor is the communication, because the systems are usually distributed, the network for data transference becomes itself an important point in these processes. Because this network should be capable to provide the exchange of data and to guarantee the demands that are imposed by the automation process. In this context, this doctorate thesis proposed, specified, analyzed and validated the Multicycles Protocol for Hospital Automation (MP-HA), which is customized to assist the demands in these automation processes, seeking to guarantee the determinism in the communications and to optimize the factor of use of the mean of transmission